Identification and analysis of actors in the supply chain of post-harvest tools (case study: teratak village, kampar district) - Mhd Andry Kurniawan; Rahmadini Payla Juarsa; Angga Pramana; Nur Hasnah AR; Imelda Yunita; Arum Rovarti Ningsih (AGROINTEK, 2026)
There is still a lack of clear understanding regarding the structure of the supply chain for palm oil post-harvest tools in Teratak Village, including the flow of goods, money, and information as well as the roles of each actor in that supply chain, even though the demand for these tools is quite high and important to support the productivity of oil palm plantations. This study aims to analyze and define the supply chain structure of post-harvest tools for oil palm from upstream to downstream. This study was carried out in Teratak village, Kampar Regency. Methods used are qualitative descriptive and BPMN (business process modeling notation) methods. Based on the study's results, it is known that the post-harvest tooling supply chain structure for oil palm starts with iron purchasing suppliers, independent blacksmith industries, blacksmith cooperatives, distributors, and consumers. From these factors comes the flow of goods, the flow of information, and the flow of money. All these factors are interrelated. The strategy that can be applied in this case is to optimize all relevant factors, namely iron collectors, blacksmith industry, blacksmith cooperatives, and distributors, to increase productivity in each element.